Biocompatibility and Biofunctionality of Magnetic Nanoparticles. (10th March 2015) - Ota, S; Yamada, T; Takemura, Yasushi
Abstract : Biocompatible magnetic nanoparticles (MNPs) have been researched for bioapplications such as imaging for diagnostics, drug delivery, hyperthermia and gene delivery. In addition, MNPs are functionalized for dispersion, biocompatibility and enhancement of therapeutic effects. In this study, polyethylenimine (PEI)-coated MNPs were prepared. The localization of PEI and PEI coated MNPs in a cell was observed with phase contrast and fluorescent microscopy and transmission electron microscopy (TEM). In addition, PEI coated MNPs were conjugated with DNA for application to magnetofection. The size distribution of preinternalized DNA/PEI/MNPs complexes after applying a dc magnetic field was measured. The size of preinternalized complexes was compared to that of internalized complexes measured by TEM. Moreover, the effect of a protein corona on cellular uptake was confirmed by size measurement and transfection experiment.